Identifikasi Minat Konsumen Ditinjau Dari Harga dan Kualitas Produk Studi Susu Kambing Etawa Desa Liman Sari - Rahfi Nurazizah; Nur Syamsiyah; Yuyun Yunarti (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to examine and evaluate the effect of price and product quality on the interest in purchasing goat milk in the residents of Liman Sari Village. This study uses a quantitative causal research methodology. The population of this study was 800 people of productive age (20-40 years) so that 89 samples were obtained using the Slovin formula. This study used a questionnaire as a data collection method. Data analysis techniques used include research instrument testing (validity and reliability tests), classical assumption tests (normality, heteroscedasticity, and multicollinearity tests), multiple linear regression analysis, evaluation of the coefficient of determination, and hypothesis testing (t-test and f-test) using SPSS version 25. The results of this study indicate that price has a positive and significant effect on purchasing interest, while product quality also has a positive and significant effect on purchasing interest. The price and product quality factors together have a positive and quite large effect on purchasing interest.